2015
DOI: 10.7314/apjcp.2015.16.12.4987
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Serum Isoflavone, Adiponectin and Insulin Levels with Risk for Epithelial Ovarian Cancer: Results of a Case-control Study

Abstract: Background: The aim of this study was to examine the association of serum isoflavones, adiponectin, and insulin levels with ovarian cancer risk. Materials and Methods: We gathered cases with histologically confirmed epithelial ovarian cancer at Sapporo Medical University Hospital from October 2010 to September 2012. Potential controls were recruited from female inpatients without any history of cancer or diabetes mellitus in different wards of the same hospital over the same period of time. Serum isoflavones, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…We observed that the increase in risk associated with irregular cycles was greatest among women with who were overweight or obese (BMI≥25). In addition to elevated androgen levels women who have irregular cycles and are additionally overweight or obese are more likely to suffer other metabolic abnormalities including insulin resistance, and limited cross-sectional evidence suggests that elevated insulin levels may be associated with ovarian cancer risk (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the increase in risk associated with irregular cycles was greatest among women with who were overweight or obese (BMI≥25). In addition to elevated androgen levels women who have irregular cycles and are additionally overweight or obese are more likely to suffer other metabolic abnormalities including insulin resistance, and limited cross-sectional evidence suggests that elevated insulin levels may be associated with ovarian cancer risk (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies addressed obesity as an important risk factor for ovarian cancer even though the mechanisms involved in the tumorigenesis have not been fully clarified [96,97,98,99,100]. Aberrant production of hormonal factors, adipokines and cytokines, and adipose related inflammatory reactions associated with obesity may affect ovarian cancer development [101,102,103,104,105]. Interestingly, several studies linked low plasma levels of adiponectin with ovarian tumorigenesis [105,106,107].…”
Section: Adiponectin In Female Cancersmentioning
confidence: 99%
“…Aberrant production of hormonal factors, adipokines and cytokines, and adipose related inflammatory reactions associated with obesity may affect ovarian cancer development [101,102,103,104,105]. Interestingly, several studies linked low plasma levels of adiponectin with ovarian tumorigenesis [105,106,107]. A Kaplan–Meier survival analysis provided evidences that, in a large cohort of women affected by ovarian cancer, high leptin/adiponectin ratio correlated with a poor outcome [108].…”
Section: Adiponectin In Female Cancersmentioning
confidence: 99%
“…In several studies has been observed a negative correlation between circulating adiponectin levels and the risk of developing certain types of cancer such as colorectal, breast, pancreatic, liver and prostate cancer 93-96. Low adiponectin levels are potentially associated with carcinogenesis 97-99. The adiponectin protective effects in tumors also include the inhibition of leptin proliferative signaling and inducing cell apoptosis 100-101.…”
Section: Introductionmentioning
confidence: 99%